2022
DOI: 10.1021/acssuschemeng.2c01054
|View full text |Cite
|
Sign up to set email alerts
|

Batch Mixing for the In Situ Grafting of Epoxidized Rubber onto Cellulose Nanocrystals

Abstract: Cellulose nanocrystals (CNCs) are sustainable nanomaterials commonly employed as biofillers in polymer composites. However, they disperse poorly in hydrophobic polymers in their pristine state, leading to premature failure under stress. Thus, there is an ongoing research effort to enhance the dispersion of CNCs in various polymer matrices to obtain their touted reinforcing potential. In this work, the CNC formation of covalent grafts with epoxidized natural rubber (ENR) and the formation of secondary hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…This indicated that although these groups took part in hydrogen bond formation, more C-O-C bonds were generated from the epoxy ring opening and subsequent ether bond formation. 27 Therefore, these results provide further evidence that grafting has occurred between the ENR and glucan, which was previously observed by FTIR measurements.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…This indicated that although these groups took part in hydrogen bond formation, more C-O-C bonds were generated from the epoxy ring opening and subsequent ether bond formation. 27 Therefore, these results provide further evidence that grafting has occurred between the ENR and glucan, which was previously observed by FTIR measurements.…”
Section: Resultssupporting
confidence: 85%
“…48 Overall, the incorporation of the glucan in the ENR system led to a higher viscosity of the composite, which can be associated with the occupation of the free volume of the ENR matrix succeeded by restriction of the ENR chains movement. 27,49 It was evident that using a catalyst for producing the masterbatch composite positively correlates with the viscosity increase as composites with a catalyst displayed greater viscosity than the samples without a catalyst. This could be attributed to the formation of more irreversible ether bond grafting of the ENR onto the glucan with the assistance of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the rubber industry is highly dependent on nonrenewable petroleum-based materials for manufacturing of their products, which has a tremendous impact on global concerns like CO 2 emission and overexploitation of natural resources. This poses threats for their business and society as well as the environment and drives toward the development of energy-efficient and environmentally friendly products which are less dependent on fossil resources. During the past few decades, this problem has been addressed by replacement of one of the inevitable and voluminous petrochemical rubber additives, carbon black filler with mineral based silica. , These fillers, when incorporated, can remarkably enhance the mechanical and dynamic properties of the green (nonreinforced) rubber. Though silica technology meets the desired performance criteria of certain rubber products, in particular passenger car tire treads, it is still not feasible to meet the sustainability goals as the manufacturing process involves nonrenewable chemicals.…”
Section: Introductionmentioning
confidence: 99%